Effects of antioxidant vitamins C and E on endothelial function and thrombosis/fibrinolysis system in smokers - Antoniades, Charalambos; Tousoulis, Dimitris; Tentolouris, Costas; Toutouza, Marina; Marinou, Kyriakoula; Goumas, George; Tsioufis, Costas; Toutouzas, Pavlos; Stefanadis, Christodoulos (Thrombosis and Haemostasis, 2003)
Smoking is associated with endothelial dysfunction and abnormalities in thrombosis/fibrinolysis system, possibly through increased oxidative stress. In this study we investigated the effect of combined antioxidant treatment with vitamins C and E on endothelial function and plasma levels of plasminogen activator inhibitor (PAI-1), von Willebrand factor (vWF), tissue plasminogen activator (tPA) and factor VII (fVII), in smokers. Forty-one healthy smokers were randomly divided into 4 groups receiving vitamin C 2g/day (group A), vitamin C 2g/day plus vitamin E 400IU/day (group B), vitamin C 2g/day plus vitamin E 800IU/day (group C) or no antioxidants (controls, group D), for 4 weeks. Forearm blood flow was measured using venous occlusion strain-gauge plethysmography. Forearm vasodilatory response to reactive hyperemia (RH%) or to sublingual nitroglycerin administration (NTG%) were considered as indexes of endothelium dependent or independent dilation respectively. After treatment, RH% was increased only in groups B (p <0.05) and C (p <0.001) but not in groups A and D. Plasma levels of PAI-1 and vWF were decreased only in group C (p <0.05 for both), while PAI-1/tPA ratio was significantly decreased in both groups B and C (p <0.05 for both). NTG% and plasma levels of tPA and fVII remained invariable in all groups. In conclusion, combined administration of vitamin C and vitamin E at high dosages, improved endothelial function and decreased plasma levels of PAI-1, vWF and PAI-1/tPA ratio in chronic smokers.
Keywords: Smoking; endothelium; thrombosis/fibrinolysis; nitric oxide; antioxidants